Recent advances in the literature on capital flow management - Roland Beck; Juan Carlos Berganza; Axel Brüggemann; Rafaël Cezar; Carlijn Eijking; Markus Eller; Alberto Fuertes; Joel Graça Alves; Lilian Kreitz; Clément Marsilli; Isabella Moder; Luis Molina; et al. (European Central Bank (ECB), 2023)
Large swings in cross-border capital flows can have consequences for domestic stability and open a channel for the transmission of shocks and spillovers across economies, including the euro area. Against this backdrop, the present paper reviews new evidence for the effectiveness of capital flow management policies in achieving macroeconomic and financial stability. Particular attention is paid to literature that has been used by the International Monetary Fund (IMF) to underpin its so-called Integrated Policy Framework, in which the roles of monetary, exchange rate, macroprudential and capital flow management policies are considered jointly. The literature published since the global financial crisis continues to affirm the effectiveness of capital flow management measures (CFMs) in addressing financial stability risks resulting from capital flow reversals; at the same time, however, it also continues to underscore that such policies should not substitute for warranted economic adjustments and structural reforms. Even so, recent literature also provides a case for considering, under certain circumstances, "precautionary" CFMs which could be applied to capital inflows to prevent a boom-and-bust cycle from being set in motion. This paper also highlights the need for further work on the longterm effects of such precautionary instruments, as well as their joint use with monetary policy instruments. Regarding capital flow management policies within the domain of central banks, the literature points to the usefulness of foreign exchange interventions (FXIs) in mitigating financial stability risks in countries with specific characteristics such as currency mismatches, borrowing constraints and shallow foreign exchange markets that are common to emerging market and developing economies alike. However, the literature also warns that such measures may reduce economic agents' incentives to hedge against currency risks, with the result that unfavourable initial conditions become further entrenched. More research is therefore needed to better understand the long-run effects of FXIs with respect to financial development and central bank credibility.
Keywords: F32; F38; 330; capital controls; short-term capital movements